Who breathes and smells according to Empedocles? On the Ï€Î±Î½Ï„Î± of fr. 96. 1 Gallavotti - Piergiacomi, Enrico (Revista Archai, 2018)
Aristotle (Resp. 473a-474a), Theophrastus (Sens. 9 and 20-22) and Demetrius of Laco (PHerc. 1012, col. 65) preserve Empedocles’ extensive account in verses of the mechanism of breathing and smell. However, this explanation does not explicitly say how many living beings actually possess such a faculty. Empedocles just begins his account with the claim that “everyone” (Ï€Î¬Î½Ï„Î±) breathes and smells, which is an ambiguous claim. It could mean both that every living being can inhale air and odor, or that only all those living beings whose respiratory organs are structured as outlined in Empedocles’ verses can do so. I will argue in favor of the first hypothesis, by studying Empedocles’ usus scribendi and his use of the word Ï€Î¬Î½Ï„Î± in other contexts. After this, I will try to defend the possibility that Empedocles’ knowledge of the mechanism of breathing and smell may have been used: 1) to heal men and women, 2) to claim that all living beings are akin, since they inhale the same air, 3) to experience the divine through some special olfactory experiences.